Association of normoalbuminuria and microalbuminuria with the components of metabolic syndrome in Bangladeshi adults - Saadi, Muntakim Mahmud; Tania, Farida Akhter; Roy, Manindra Nath; Haque, Rubena; Mishu, Farzana Akonjee; Huq, Gaziul (BIRDEM Medical Journal, 2020)
Background: Metabolic syndrome (MetS) is clustering of metabolic abnormalities characterized by obesity, hypertension, dyslipidemia and glucose intolerance that collectively increases the risk of diabetes mellitus, cardiovascular disease, stroke and overall mortality. Microalbuminuria is associated with diabetes mellitus, hypertention, obesity all are components of metabolic syndrome. Microalbuminuria and MetS have both been linked to chronic kidney disease and cardiovascular disease. Before development of microalbuminuria there is a wide normal range for urinary albumin excretion. By comparing the strength of the association between MetS and its components with normoalbuminuria and microalbuminuria, we can assess the risk of cardiovascular and renal diseases. This study aimed to evaluate the association of normoalbuminuria and microalbuminuria with the components of MetS in Bangladeshi adult subjects. Methods: It was a cross-sectional analytical study, carried out in the Department of Biochemistry of Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh during the period of March 2017 to January 2018. Total 175 patients with MetS attending the outpatient department of Medicine and Endocrinology of Mitford Hospital were included. Collected data was checked, edited and analyzed with the help of software SPSS (Statistical Package for Social Sciences) version 22. Results: This study showed, among the total 175 study subjects, 125 subjects were with normoalbuminuria (71.43%) and 50 subjects had microalbuminuria (28.57%). With an average age 42.4 years, female were 52% in this study. There was also female predominance among microalbuminuric subjects (13.71% vs 14.75%). Participants with microalbuminuria were more likely to have higher systolic blood pressure (SBP), diastolic blood pressure (DBP) and fasting blood glucose (FBG) than those with normoalbuminuria. The albumin creatinine ratio (ACR) of study subjects ranged from 3.00 to 270.39 mg/g and mean ACR was 27.14 mg/g. The mean ACR for participants with three (n=34), four (n=72) and five (n=69) components of MetS were 14.73, 19.94 and 40.77 mg/g respectively and corresponding prevalence of microalbuminuria was 10%, 32% and 58% respectively. Normal range of urinary albumin excretion rate (normoalbuminuria) were classified into four quartiles according to their ACR values and ranges for Q1, Q2, Q3 & Q4 were respectively Q1 = 3.00 to 5.1, Q2 = 5.1 to 8.2, Q3 = 8.2 to 13.89, Q4 = 13.89 to 28.1mg/g. The means of elevated DBP, SBP, FBG and tri-acyl glycerol (TAG) among the components of MetS showed increasing trend from lower to upper quartiles within normal range. Q1 was considered as base line in comparison to other quartiles. Odds of elevated WC, FBG, TAG, BP and low HDL-C were high across increasing quartiles of ACR (1.00 vs 1.33 vs 2.24 vs 1.79 respectively for central obesity; 1.00 vs 1.07 vs 1.97 vs 2.07 respectively for elevated fasting blood glucose; 1.00 vs 1.51 vs 1.69 vs 1.69 respectively for elevated TAG; 1.00 vs 6.86 vs 3.87 vs 2.88 respectively for elevated BP and 1.00 vs 1.35 vs 2.79 vs 2.79 respectively for low HDL-C; p-values <0.05 for all). Among the components of MetS, most significant relationship was observed between elevated BP and increasing ACR quartile within normal range. Conclusions: In conclusion, we demonstrated that microalbuminuria was strongly associated with MetS and its components. Microalbuminuria should be reconsidered as a component of MetS as it shows incremental effect with severity of MetS. Even upper normal range of albuminuria (higher normoalbuminuria) is strongly associated with elevated BP, FBG and TAG among the components of MetS. So, normal range of albuminuria should be rearranged after performing large scale population study in this regard. Birdem Med J 2020; 10(3): 152-158